Tracing the Distribution of European Lactase Persistence Genotypes Along the Americas - Chana-Cuevas, P (Frontiers Media S.A., 2021)
In adulthood, the ability to digest lactose, the main sugar present in milk of mammals, is a phenotype (lactase persistence) observed in historically herder populations, mainly Northern Europeans, Eastern Africans, and Middle Eastern nomads. As the –13910∗T allele in the MCM6 gene is the most well-characterized allele responsible for the lactase persistence phenotype, the –13910C > T (rs4988235) polymorphism is commonly evaluated in lactase persistence studies. Lactase non-persistent adults may develop symptoms of lactose intolerance when consuming dairy products. In the Americas, there is no evidence of the consumption of these products until the arrival of Europeans. However, several American countries’ dietary guidelines recommend consuming dairy for adequate human nutrition and health promotion. Considering the extensive use of dairy and the complex ancestry of Pan-American admixed populations, we studied the distribution of –13910C > T lactase persistence genotypes and its flanking haplotypes of European origin in 7,428 individuals from several Pan-American admixed populations. We found that the –13910∗T allele frequency in Pan-American admixed populations is directly correlated with allele frequency of the European sources. Moreover, we did not observe any overrepresentation of European haplotypes in the –13910C > T flanking region, suggesting no selective pressure after admixture in the Americas. Finally, considering the dominant effect of the –13910∗T allele, our results indicate that Pan-American admixed populations are likely to have higher frequency of lactose intolerance, suggesting that general dietary guidelines deserve further evaluation across the continent. © Copyright © 2021 Guimarães Alves, Sukow, Adelman Cipolla, Mendes, Leal, Petzl-Erler, Lehtonen Rodrigues Souza, Rainha de Souza, Sanchez, Santolalla, Loesch, Dean, Machado, Moon, Kaplan, North, Weiss, Barreto, Lima-Costa, Guio, Cáceres, Padilla, Tarazona-Santos, Mata, Dieguez, Raggio, Lescano, Tumas, Borges, Ferraz, Rieder, Schumacher-Schuh, Santos-Lobato, Chana-Cuevas, Fernandez, Arboleda, Arboleda, Arboleda-Bustos, O’Connor, Beltrame and Borda.